Cyber Security for Smart Grid, Cryptography, and Privacy. (4th October 2011) - Iyer, Swapna
Abstract : The invention of "smart grid" promises to improve the efficiency and reliability of the power system. As smart grid is turning out to be one of the most promising technologies, its security concerns are becoming more crucial. The grid is susceptible to different types of attacks. This paper will focus on these threats and risks especially relating to cyber security. Cyber security is a vital topic, since the smart grid uses high level of computation like the IT. We will also see cryptography and key management techniques that are required to overcome these attacks. Privacy of consumers is another important security concern that this paper will deal with.